Nd’awakananawal Babijigwezijik Wd’elasawawôganôl: “We Wear the Clothing of Our Ancestors” - Sheehan, Vera Longtoe (DigitalCommons@University of Nebraska - Lincoln, 2018)
When thinking of Native American people, a typical image is of tanned people with long dark hair wearing leather and furs in the distant past, but that is not an accurate depiction of the Abenaki people or their textiles. As an Abenaki scholar, artist, and educator, my research into the textile traditions of the Abenaki people includes archaeological evidence, primary resources, and oral history interviews. Abenakis themselves have different ideas of what it traditional because textile and fiber arts evolved over many millennia throughout N’dakinna, the Abenaki homeland which once encompassed Vermont, New Hampshire, northern Massachusetts, and parts of New York, Maine, and Quebec. Archaeological evidence found in Vermont suggests that prior to European contact, Abenaki people were wearing sophisticated textiles comprised mostly of milkweed and other plant fibers. Memoirs of 17th century French explorers Samuel de Champlain and Marc Lescarbot refer to Indigenous populations from N’dakinna was wearing “chamois” or leather. During the Seven Years War, a French officer named Pierre Pouchot described traditional garments made from trade cloth worn by Native American people in the region. Family photographs from the Civil War era and early 20th century provide glimpses of distinctly Native clothing such as a young girl’s peaked hood or a man’s leggings worn with otherwise conventional garb. My research into Abenaki textile traditions reveals connections between the archaeological and historical records and interview with living Abenaki informants to reveal how textiles were and are still used not only for warmth and protection but to reflect Abenaki heritage and to express native identity. Regalia is still made and worn for self-affirmation, to affirm connections with family, clan, band, and tribe, and to express identity within the geographical locale co-occupied with mainstream culture. This study reveals both continuity and change within the textile traditions of a little known Indigenous culture.